Self-assessment of P.O.C.U.S. use in the clinical practice of anesthesia and intensive care by medical residents after completion of simulation training on a high-fidelity simulator - Simon, Robert; Petrisor, Cristina; Bodolea, Constantin; Antal, Oana; Vasian, Horatiu Nicolae; Puia, Ion Cosmin (Medicine and Pharmacy Reports, 2025)
Background. Simulation based education and training (SBET) is an important part of formal medical education and training, with anesthesia and intensive care domains being among the first to use this teaching method. Implementation of SBET into anesthesia and intensive care training is included in the recommendations lists of the European Society of Anesthesia and Intensive Care, with Point of Care Ultrasound (POCUS) being on the list of procedures that residents should be trained in using SBET. Objectives. In this study the objective is to assess the clinical use of POCUS by trainees in Anesthesia and Intensive Care that finished a simulation program on a high-fidelity simulator. Methods. We developed a questionnaire comprised of seven sections that evaluates the use of POCUS in clinical practice related to airway, lung, cardiac ultrasound, the availability of POCUS, possible barriers that create limitations, as well as scoring and feedback regarding the simulation sessions and distributed it to trainees that finished the simulation sessions. Results. Over 90% of respondents declare using POCUS in their daily clinical practice, with more use of pulmonary evaluations than cardiac evaluations. Most of the responders declared good or very good knowledge and ability to diagnose most of the critical conditions described in the curriculum for lung and cardiac POCUS. Conclusions. Self-assessment methods may be used alongside traditional methods to offer a wider view on POCUS competency and maintenance of skills of trainees in anesthesia and intensive care.